THE HEROIC IDEAL IN BEOWULF: PAGAN COURAGE AND CHRISTIAN MORALITY - Kuatbaeva Sayatxan Maxmudovna, Scientific adviser: Khamitov Eldorbek E. (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This study examines the heroic ideal in Beowulf through the connection between pagan courage and Christian morality. As an early English epic, the poem reflects a cultural transition in which traditional Germanic values coexist with emerging Christian beliefs. Through Beowulf’s major battles and his final sacrifice, the narrative shows how courage gains deeper meaning when guided by moral intention and faith. The study concludes that Beowulf successfully merges two worldviews, presenting a heroic ideal that resonates across time.